Recruiting and Selection during the Era of Umar Bin Khattab Administration - Bolatito, Samtito Shamsuddin (IJIBE (International Journal of Islamic Business Ethics), 2024)
The Era of Umar Ibnul Khattab is considered as the golden age in the history of Islam, The public treasury (Baitul mal), Army bureau, department of Records (Diwan), Hisba were all initiated in his time which led to signifying recruitment. This comprehensive paper explores the subject of recruitment and selection during the reign of Umar ibn Khattab, the second caliph of the Rashidun Caliphate. The reign of Umar bin Khattab from 634 to 644 AD saw notable progress in administrative structures, such as the implementation of a well-organized recruiting and selection procedure. This study examines the strategies used by Umar bin Khattab to find and choose persons for important roles within the Islamic state. Utilizing reputable print encyclopedias, nonfiction books, academic journals, and dictionaries, this study offers a comprehensive examination of the historical backdrop, selection criteria, and the influence of Umar bin Khattab's approach on the governance of the caliphate.This paper further describes and analyzes job recruitment and selection in this era. The method used in this research is a descriptive approach, the recruitment policy, and its process were described. And the data were collected from secondary sources. The research found that his employment of experts regardless of closeness or any other factor was the main characteristic of his era, his policies and procedures in recruiting can be used to establish an Islamic recruitment policy and structure.